Fra armesterke bondesønner til akademikerbarn - Paul Larsson (Nordisk Tidsskrift for Kriminalvidenskab)
This article documents the movement of the Norwegian police away from the recruitment of "arm strong country boys" at the end of the 1960 's in favour of the sons and daughters of the relatively well-educated middleclass. The myth of the strong country boy is well supported by research. Today, however, police students generally come from towns and smaller cities, and as much as 70 percent of them have parents with university or college degrees. The article describes when this change occurred, and explores whether it resulted in more "academic "police officers and how the change in recruitment can be explained. The most surprising finding is that the motivation for choosing a career in the police has not changed substantially for the last 40 years. The most common reason for wanting to become a police officer is that it is an occupation with multiple and varying tasks, that it allows work with people, and that it is seen as a stable, secure Job. There is little if any indication that the students today are more "academic" in their perceptions of the work than before. What is more striking, in fact, is their similarity in world view. This suggests that there is a certain type of middle-class child that is attracted to the profession. Regarding the timing of the change, some indicators suggest the end of the 1970 's as the watershed, though it has actually been a gradual movement over the last 40 years. Explanations for the change are mainly found outside the police force. One is the gradual rise in level of education within the Norwegian population, white another is the increased social status and professionalization of the Norwegian police.